1994
DOI: 10.1002/ajhb.1310060206
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of blood pressure and lipid levels among Marwaris of Calcutta, India

Abstract: This population based study was conducted among the Marwaris of Calcutta, India. A total of 1,096 individuals from 151 randomly selected families were studied. Mean blood pressures were high. About 17% of the population was hypertensive, i.e., systolic blood pressure > 160 mm Hg and/or diastolic blood pressure > 95 mm Hg. The mean value of the ratio of total cholesterol to HDL cholesterol was 4.75. Comparison with a rural agricultural population showed that unadjusted blood pressure profiles differed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…Nevertheless, the socioeconomically most advanced population in group IV showed the largest mean DBP in males but not in females. This is consistent with the general observation, that compared to traditional populations, urbanized groups tend to show on average, higher blood pressures (Padmavathi and Gupta, 1959;Dalal, 1978;Rao, 1983;Dressler et al, 1987;McGarvey et al, 1989;Fleming Moran et al, 1991;Pollard et al, 1991;Majumder et al, 1994). The trend in females is less marked and different from that in males was also observed by others (Salmond et al, 1989;Fleming-Moran et al, 1991;Jiang He et al, 1991).…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, the socioeconomically most advanced population in group IV showed the largest mean DBP in males but not in females. This is consistent with the general observation, that compared to traditional populations, urbanized groups tend to show on average, higher blood pressures (Padmavathi and Gupta, 1959;Dalal, 1978;Rao, 1983;Dressler et al, 1987;McGarvey et al, 1989;Fleming Moran et al, 1991;Pollard et al, 1991;Majumder et al, 1994). The trend in females is less marked and different from that in males was also observed by others (Salmond et al, 1989;Fleming-Moran et al, 1991;Jiang He et al, 1991).…”
Section: Discussionsupporting
confidence: 87%
“…60 individuals out of 450 were found to be hypertensive. This prevalence rate (13.3%) is higher than in many agricultural communities, but is similar to that of many semi-urban and urban popula tions [10], In all. 370 blood samples were available for analysis of ACE (I/D) polymor phism (59 hypertensives and 311 normotensives).…”
Section: Resultsmentioning
confidence: 92%
“…The hypertensives and normotensives have a very similar socio-eco nomic status, dietary habits and were free of any known heart conditions; therefore it is unlikely that this is a chance observation. Also there is a slightly higher prevalence of hyper tension in this population compared to many rural populations of India [10], but it is not clear whether this is due to becoming settled agriculturists or whether there is some other genetic/biological explanation. Further stud ies will help in elucidating genetics of hyper tension in this population.…”
Section: Discussionmentioning
confidence: 98%
“…Earlier studies on Indian populations [20][21][22] also showed a greater prevalence of coronary heart disease and risk factors in urban subjects. In a population-based study among Marwaris of Calcutta, 23 the Marwaris had 17% of hypertensives and the means of SBP, DBP, TC and HDLc were 125.30 mmHg, 82.28 mmHg, 176.86 mg/dL and 41.06 mg/dL, respectively. Although the results of our study showed similar findings, no significant difference was observed for hypertension and smoking habit between the urban and rural populations ( Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Multiple linear regression analysis of data collected from the 'Reddy' population of Southern Andhra Pradesh, India BMI, body mass index; CI, conicity index; DBP, diastolic blood pressure; HDLc, high-density lipoprotein cholesterol; SBP, systolic blood pressure; TC, total cholesterol. In a population-based study among Marwaris of Calcutta,23 the Marwaris had 17% of hypertensives and the means of SBP, DBP, TC and HDLc were 125.30 mmHg, 82.28 mmHg, 176.86 mg/dL and 41.06 mg/dL, respectively. Earlier studies on Indian populations[20][21][22] also showed a greater prevalence of coronary heart disease and risk factors in urban subjects.…”
mentioning
confidence: 96%